(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
The current research aims to identify the level of strategic behavior in the organization in question and its impact on organizational excellence. The organization in question was the University of Karbala, and the sample included senior leaders from department managers and above, with some (85) people. A strategy followed by the organization under study was based on the model (Miles and Snow, 1978) and its impact on achieving organizational excellence, and some statistical methods were relied on to process the data obtained from the questionnaire from the (spss) and (Amos.23) program, such as percentages and arithmetic mean The standard deviation, the coefficient of variation, the normal test, and the certainty factor, and to know the correlation between the two variables, the simple correlation coefficient (Pearson) was relied upon. As for the effect of the independent variable on the dependent, the simple regression coefficient was used. The surveyed organization suffers from a decrease in the number of young leaders occupying leadership positions and the existence of a complex hierarchical organizational structure that is reflected this is due to the slowness of the procedures they are taking. The current research recommended conducting training courses to qualify leaders in the university administration to be able to achieve administrative excellence, which is reflected in human, structural, and strategic excellence.